BIOLOGIYA DARSLARIDA ZAMONAVIY PEDAGOGIKA VA AXBOROT TEXNOLOGIYALARDAN FOYDALANISHNING SAMARADORLIGI (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the effectiveness of the effective use of modern pedagogical technologies and information and communication technologies (ICT) in teaching biology. The study highlights the theoretical and methodological foundations of organizing the educational process based on innovative approaches, and reveals the possibilities of using interactive methods, multimedia tools, virtual laboratories, and digital educational platforms in biology lessons.